Removal of albumin from platelet lysates for the fabrication of hydrogels for 3D cell culture - Loureiro, Ana Miguel da Silva (2021)
The transition from the second to the third dimension is crucial to improve the reliability and predictive ability of cell-based assays, motivating the development of in vitro systems that could recapitulate the physiological cellular microenvironment. Proteins naturally occurring in the human body have been attracting attention as biomaterials for scaffold fabrication, due to their biochemical similarity with native tissues and potential allogenic source. In this context, METATISSUE has developed a novel photopolymerizable hydrogel based on human platelet lysates (PL) proteins to improve cell adhesion.